2020
DOI: 10.2217/nnm-2019-0169
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Brain Delivery: A Guide to Verification Methods

Abstract: Many reports conclude nanoparticle (NP) brain entry based on bulk brain analysis. Bulk brain includes blood, cerebrospinal fluid and blood vessels within the brain contributing to the blood–brain and blood–cerebrospinal fluid barriers. Considering the brain as neurons, glia and their extracellular space (brain parenchyma), most studies did not show brain parenchymal NP entry. Blood–brain and blood–cerebrospinal fluid barriers anatomy and function are reviewed. Methods demonstrating brain parenchymal NP entry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 139 publications
2
28
0
Order By: Relevance
“…Even if nanoparticles reach the cerebrospinal fluid, they still cannot directly access the brain parenchyma because of the ependymal/glial barrier. Only a tiny proportion of drugs injected into the blood or ventricles normally reaches the brain parenchyma; for this reason, it is essential when quantitating transport to verify exactly where in the brain the drug/treatment is located [ 19 ].…”
Section: Barriers For Nanoparticle Transport Into the Cnsmentioning
confidence: 99%
“…Even if nanoparticles reach the cerebrospinal fluid, they still cannot directly access the brain parenchyma because of the ependymal/glial barrier. Only a tiny proportion of drugs injected into the blood or ventricles normally reaches the brain parenchyma; for this reason, it is essential when quantitating transport to verify exactly where in the brain the drug/treatment is located [ 19 ].…”
Section: Barriers For Nanoparticle Transport Into the Cnsmentioning
confidence: 99%
“…Few studies demonstrated nanoparticle entry into brain parenchyma after i.n. administration that met established criteria (Yokel, 2020). Cited studies that gave the nanoparticle intranasally showed evidence that chitosan increased brain or CSF uptake from the nasal cavity, but none showed intact nanoparticle translocation into brain parenchyma (Casettari & Illum, 2014).…”
Section: Demonstration Of Brain Parenchyma Nanomedicine Deliverymentioning
confidence: 99%
“…The BMECs present a single layer of compact, almost nonfenestrated endothelial cells, sealed together by tight junctions. The efflux transporters of BMECs prevent the entry of arbitrary substances, ions and enzymes, in the brain parenchyma while the influx transporters allow the inward movement of essential nutrients and necessary factors to the brain cells [21]. The BBB, thus, competently sustains the brain homeostasis and functional and architectural integrity.…”
Section: Treatmentmentioning
confidence: 99%
“…For greater access to the CNS of NPs, the nasal route of drug delivery has become popular as of late. The roof of the nasal palate is perhaps the sole region of the body where direct uptake of NP into the CNS, bypassing the BBB, is a possibility [21]. It is also advantageous that TBI often results in leaky BBB making NP drug delivery feasible.…”
Section: Nanomedicine For Tbimentioning
confidence: 99%